2022
DOI: 10.5194/acp-2022-406
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global Distribution of Asian, Middle Eastern, and Saharan Dust Simulated by CESM1/CARMA

Abstract: Abstract. Dust aerosols affect the radiative and energy balance at local and global scales by scattering and absorbing sunlight and infrared light. Parameterizations of dust lifting, microphysics, as well as physical and radiative properties of dust in climate models are still subject to large uncertainty. Here we use a sectional aerosol model (CARMA) coupled with a climate model (CESM1) to investigate the global distribution of dust aerosols, with an emphasis on the vertical distribution of dust. Consistent w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…An excellent overview of different dust dispersion models is given by Holmes and Morawska (2006). (Lian et al, 2022) recently used a sectional aerosol model (CARMA) coupled with a climate model (CESM1) to investigate the global distribution of dust aerosols, paying particular attention to the vertical distribution of dust. Their results suggested that Saharan, Middle Eastern, and Asian specks of dust make up ~59.7%, 12.5%, 26 and 13.3% of the global annual mean dust emissions, with the remaining 14.5% stemming from scattered smaller dust sources.…”
Section: Propagation Dynamics Of Saharan Dust Stormsmentioning
confidence: 99%
“…An excellent overview of different dust dispersion models is given by Holmes and Morawska (2006). (Lian et al, 2022) recently used a sectional aerosol model (CARMA) coupled with a climate model (CESM1) to investigate the global distribution of dust aerosols, paying particular attention to the vertical distribution of dust. Their results suggested that Saharan, Middle Eastern, and Asian specks of dust make up ~59.7%, 12.5%, 26 and 13.3% of the global annual mean dust emissions, with the remaining 14.5% stemming from scattered smaller dust sources.…”
Section: Propagation Dynamics Of Saharan Dust Stormsmentioning
confidence: 99%